Modelling of charge/discharge cycle of lithium ion battery system - Ho, Kar Yee; Sivakumar Ramakrishnan,; Ahmad Azmin Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2014)
In this paper, a general model of lithium ion battery based on specific charge/discharge profile of the battery has been developed. The governing equations are solved by explicit numerical method. The partial differential numerical simulation is performed using MATLAB software. The charge/discharge model is capable of predicting the total discharge time of a battery under various discharge rates. The simulated result is also compared to experimental data of specific condition from a specified journal. Then an equation that represents the simulation result is formulated.